Overview of Geosciences Applied to Forensic Taphonomy: The Interdisciplinary Approach of the Italian Non-Human Research Facility (Ticino-LEAFs) - Giulia Tagliabue; Anna Masseroli; Giulia Caccia; Pasquale Poppa; Cristina Cattaneo; Luca Trombino (Geosciences)
The recent surge in the application of geosciences in forensics has yielded significant insights into taphonomy and decomposition processes, particularly with regard to the identification and interpretation of evidence pertaining to the interaction between the cadaver and the outdoor post-depositional environment. Given that a substantial proportion of current knowledge about decomposition dynamics can be attributed to forensic taphonomy experiments utilizing pigs as human models, a literature review was conducted, focusing on experiments incorporating geosciences into their investigative techniques. The results demonstrated the crucial role of this approach in ensuring accurate interpretation of data, both in the context of forensic cases and in experimental research. Furthermore, this manuscript presents the opening of the first Italian non-human forensic taphonomy facility, which was inaugurated by the LABANOF of the University of Milan in 2009 at the Lombardy Park of the Ticino (PV). The facility strives to integrate the use of non-human animals as human models while upholding a high ethical standard and minimizing the construction of artifacts, thereby striving for forensic realism. Furthermore, the most recent project conducted at the Italian FTF establishes a connection between the outcomes of preceding projects and underscores the significance of a pragmatic and intellectual disposition that embraces interdisciplinary collaboration.